Impact of E-Banking Practices on Customer Satisfaction in Nepalese Commercial Banks - Regmi, Prakash; Sah, Puja (Nepalese Journal of Finance, 2025)
This study examines the impact of E-banking practices on customer satisfaction in Nepalese Commercial Banks. Customer satisfaction is selected as the dependent variable. Similarly, convenience, reliability, ease of use, security and privacy, time saving and perceived benefits are selected as the independent variables. This study is based on primary data with 121 observation. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing E-banking practices on customer satisfaction in Nepalese Commercial Banks. The study showed that that the convenience has a positive impact on customer satisfaction. It means that increase in convenience leads to increase in customer satisfaction. Similarly, reliability has a positive impact on customer satisfaction. It means that increase in reliability leads to increase in customer satisfaction. Moreover, the ease of use has a positive impact on customer satisfaction. It indicates that increase in ease of use of e-banking services leads to increase in customer satisfaction. In addition, the security has a positive impact on customer satisfaction. It indicates that increase in security of e-banking services leads to increase in customer satisfaction. Likewise, the time saving has a positive impact on customer satisfaction. It means that increase in time saving of customers leads to increase in customer satisfaction. Furthermore, the perceived/transaction benefits has a positive impact on customer satisfaction. It means that increase in perceived benefits leads to increase in customer satisfaction.